(untitled) (Collection of scientific works «Modern structures of metal and wood», 2024)
Traditional methods of beam’s structures calculation for industrial buildings’ coatings provide their consideration separately from the frame structures, in particular, reinforced concrete slabs, without taking into account their joint work, which leads to a significant safety margin of structures. Today, there is a significant number of industrial buildings and structures that require strengthening and reconstruction in Ukraine. In this regard, studies of the actual load- bearing capacity of single-storey industrial building frames are particular importance, both during reconstruction and new construction. Their results will significantly reduce costs and allow for more rational design of structures. At the same time, one of the most relevant areas is the study of the joint operation of metal load-bearing structures with precast concrete structures of hard discs coatings and slabs in their calculation. Moreover, in the Ukrainian national design standards, as well as in the educational and methodological literature, the calculation methods for taking into account the joint operation of such structures are not fully covered. The purpose of study is to assess the reduction of metal consumption for steel truss structure in its bending calculation, taking into account the joint operation with a rigid precast concrete slab disc. Method. As part of the study, It was calculated a flat roof truss from the paired corners of an one-storey industrial building according to the traditional design scheme – without taking into account the joint operation with the slab disc and taking into account the joint operation with the slabs by means of numerical modelling as part of a roof block using the finite element method. The modelling of the pavement fragment (block) was performed in LIRA FEM 2022 software. The main results. It is performed a comparative analysis of the internal forces in steel truss elements and the total mass of the truss based on the selected cross-sections of its elements by two design models. The practical significance of the obtained results is to determine the economic effect by reducing the material consumption and the degree of unloading of steel trusses as part of the roofing block of a one-storey industrial building, taking into account their joint operation with hard discs of precast concrete slabs.